Control of bacteriophage P2 gene expression: analysis of transcription of the ogr gene. - Birkeland, N K (1991)
The bacteriophage P2 ogr gene encodes an 8.3-kDa protein that is a positive effector of P2 late gene transcription. The ogr gene is preceded by a promoter sequence (Pogr) resembling a normal Escherichia coli promoter and is located just downstream of a late transcription unit. We analyzed the kinetics and regulation of ogr gene transcription by using an ogr-specific antisense RNA probe in an S1 mapping assay. During a normal P2 infection, ogr gene transcription starts from Pogr at an intermediate time between the onset of early and late transcription. At late times after infection the ogr gene is cotranscribed with the late FETUD operon; the ogr gene product thus positively regulates its own synthesis from the P2 late promoter PF. Expression of the P2 late genes also requires P2 DNA replication. Complementation experiments and transcriptional analysis show that a nonreplicating P2 phage expresses the ogr gene from Pogr but is unable to transcribe the late genes. A P2 ogr-defective phage makes an increased level of ogr mRNA, consistent with autogenous control from Pogr. Transcription of the ogr gene in the prophage of a P2 heteroimmune lysogen is stimulated after infection with P2, suggesting that Pogr is under indirect immunity control and is activated by a yet-unidentified P2 early gene product during infection.